Validation and clinical application of a spectrophotometric technique for the determination of potassium bromide in canine serum for the control of epilepsy - Diego Robaina; Victoria Bentancur; Gimena Feijóo; Juan Pablo Damián; Gonzalo Suárez (GarVal Editorial Ltda., 2020)
Context: In canine patients with epilepsy, for therapeutic monitoring of seizure control by administration of potassium bromide (KBr), a validated analytical methodology is required for the quantification of serum bromide concentrations (Br-). Aims: To validate a spectrophotometric technique for the determination of serum Br- concentrations and test the applicability in the therapeutic monitoring of epilepsy in canines. Methods: We started from a serum matrix of 6 companion canines, clinically healthy and with no history of having been medicated with KBr or another drug in the last 6 months. The samples were quantified by spectrophotometry (wavelength 440 nm) at concentrations of 0, 150, 250, 500, 1000, 2000, 3000 and 4000 µg/mL of KBr, in three independent repetitions. The analytical method evaluated the parameters of linearity, accuracy, precision, limit of detection, limit of quantification and absolute recovery. Results: Linearity was checked for the range of 150 to 3000 µg/mL (R2 > 0.99), with accuracy and precision values of 97.3% and 9.4%, respectively. The detection limit was established at 96 µg/mL and the quantification limit at 150 µg/mL of KBr. The absolute recovery of the test reached 98.4%. The values obtained for the different parameters analyzed validate the technique in the concentration range of 150 µg/mL to 3000 µg/mL, which meet the internationally established acceptance criteria. Conclusions: The paraclinical results obtained by applying the technique in KBr-medicated epileptic canines support the validation of the technique and the therapeutic monitoring in the control of epilepsy.